A freshness indicator for monitoring chicken-breast spoilage using a Tyvek® sheet and RGB color analysis. (March 2019) - Lee, Kaeun; Baek, Seunghye; Kim, Dowan; Seo, Jongchul
Highlights: Three-layered structure of freshness indicator was prepared using a porous Tyvek ® . The color change of freshness indicator was adjustable by the content of pH dye. The freshness indicator represented the quality change of chicken breast successfully. The color difference (RGB) was obtained from a digital image taken by smartphone. The freshness indicator exhibited no dye migration by using Tyvek ® . Abstract: In this study, a simple, inexpensive, and high-confidence freshness indicator was developed to detect chicken-breast spoilage using a pH-sensitive dye, bromocresol green (BCG); color changes in the freshness indicator were analyzed using RGB digital images. The indicator consisted of a three-layered structure, using a Tyvek ® sheet with high gas and vapor permeability as the inner layer, BCG-immobilized with the binding polymer as the color-changing layer, and a low-density polyethylene film as the outer layer. Color changes in the indicator were correlated with CO2 and total volatile basic nitrogen contents and bacterial growth in the chicken breast, which were quantified using digital images captured on a smartphone. When the indicator turned yellow from green, it indicated spoilage; further, a large difference was observed in the RGB values. The proposed freshness indicator with no dye migration is highly feasible, safe, and reliable for the real-time monitoring of quality changes in chicken breasts. Digital image processing via a smartphone makes it a simple and accurate method, allowing consumers to judge food quality easily and reliably.